(3QSGdI aj GSJNQGL LjH GdOQLI GdhGMOI Ydi GdJMbjb GdMbjbs - (3GdcGTj Ch GdcGTGfj, ZjGK GdOjf, nLreTpjO Hf eSYhO Hf eMehO, J (B832 (3g`s
(3ChdgG (B:s
(3CMeOg Ydi LRjd EfYGeg hGdeHQRhf aj GdUfGYI GdeYJfhf HTCf gPg GdHVGYI eY JcKQ GdYOO hJhaQ GdYOO hceGd GdGgJeGe aj EJeGe CeKGd gPG GdeQGe Edi ReGffG gPG de jMhehG Mhd JMbjbg s
(3BNQgG (B:s
(3GdKGef VQH GdbSeI hjNJU HYOOjf eQcHjf ajVQH CMO LRFj GdeVQhH aj GMO LRFj GdeVQhH ajg hGdBNQ aj GdBNQ hjVQH CMO GdMGUdjf aj GdBNQ ajMUd GdeWdhH Jes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B2\136s
(3cTa GdXfhf (B1\844s
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdQjGVjGJs